Isoorientin Improves Excisional Skin Wound Healing in Mice - Aline B. Hora; Laiza S. Biano; Ana Carla S. Nascimento; Zaine T. Camargo; Greice I. Heiden; Ricardo L. C. Albulquerque-Júnior; Renata Grespan; Jessica M. D. A. Aragão; Enilton A. Camargo (MDPI AG, 2024)
Background/Objectives: Wound healing relies on a coordinated process with the participation of different mediators. Natural products are a source of active compounds with healing potential. Isoorientin is a natural flavone recognized as having several pharmacological properties, such as anti-inflammatory effects, making it a potential treatment for wounds. We investigated the effect of isoorientin on the healing of excisional skin wounds. Methods: Male Swiss mice were subjected to the induction of excisional skin wounds (6 mm diameter) and treated with a vehicle (2% dimethyl sulfoxide in propylene glycol) or 2.5% isoorientin applied topically once a day for 14 days. The wound area was measured on days 0, 3, 7, and 14. Histopathological analyses were performed on the cicatricial tissue after 14 days. The myeloperoxidase activity and the interleukin-1β, tumoral necrosis factor (TNF)-α, and interleukin-6 concentrations were determined on the third day. Results: We observed that 3 days after the topical application of isoorientin, the lesion area was significantly smaller when compared to those of the vehicle (p < 0.01) and control (p < 0.05) groups. No difference was observed after 7 and 14 days of induction. Despite this, on day 14, histological analysis of cicatricial tissue from the animals treated with isoorientin showed reduced epidermal thickness (p < 0.001) and increased collagen deposition (p < 0.001). These effects were accompanied by decreased myeloperoxidase activity and interleukin-1β concentration on the third day of induction, without alteration in TNF-α and interleukin-6. Conclusions: The treatment with isoorientin promoted better tissue repair in excisional wounds in mice, which may be linked to the modulation of the early inflammatory response.